Implementation of alternative therapies as a health promotion strategy in a nursing home: an experience report (Research, Society and Development, 2023)
Human aging is a natural biological process marked by a set of diverse experiences that are influenced by the multiplicity of genetic, physiological, social, environmental, psychological, and cultural factors. In this sense, the increase in this age group is associated with healthy and active aging. Thus, this work aims to train caregivers of a Philanthropic Home to implement alternative therapies with the elderly. Therefore, this work is an experience report based on the Arco de Maguerez. In which it began with a visit carried out on June 6, 2022, with the purpose of recognizing the usual reality of the institution. During the visit, it was noted that the institution has the support of a team of health professionals focused on the curative method. However, it is noteworthy that the home needs more resources, both care and administrative, to provide care and provide a better quality of life for the elderly who live in it, with two training sessions being carried out with the caregivers of the nursing home on complementary therapies. Soon, after identifying the professional and structural demands, it was suggested planning actions and activities that could be carried out in the home for the elderly, involving professionals and available resources in order to minimize the problems encountered.